UAV Path-Following Strategy for Crossing Narrow Passages - Caldeira, Alexandre G.; Vasconcelos, Joao Vitor R.; Sarcinelli-Filho, Mario; Brandao, Alexandre S. (Conference proceedings (International Conference on Unmanned Aircraft Systems. Online), 2020)
Integration of unmanned aerial vehicles in different tasks and services rely on their ability to deliberate and plan solutions to navigate an environment, which is often subject to geometric constraints that frequently cannot be tackled with classic obstacle avoidance. Therefore, we propose a smooth, closed path that ensures safe passage through challenging locations while respecting a robot's physical limitations. A novel approach for proposing control points in Bèzier curve path planning is outlined and a multi-layer control scheme is presented and validated in simulation and experiments with a varying number of robots and restrictions in motion.